Analysis of methodological approaches of armies of the world countries in the context of the development of psychological training of military personnel for combat operations - Vasyliev, Serhii (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2024)
Background. The military aggression of the Russian Federation against Ukraine raised new requirements for the comprehensive training of military personnel, in particular, psychological training for combat operations. The movement towards compliance with NATO standards is alsoconfirmed by the experience of conducting combat operations by units of the Armed Forces of Ukraine. The introduction of the latest approaches in training provides the necessary impetus, becoming a trend of increasing the effectiveness of military personnel on the battlefield.Methods . The source base of the research consists of documents of the armies of NATO countries, professional literature in the field of psychology, publications in professional psychological issues. The method of review and analytical research of the literature was used – to find out the methodological approaches to conducting psychological measures for the training of the personnel of the armies of NATO countries.Results . The analysis shows that NATO countries and other developed countries are guided by the developments and experience of the US Army in training military personnel for combat operations. The main priorities for the training of the US Army are the training of command staff withhigh adaptability and the training of highly professional personnel. The basis of the psychological training of military personnel is the formation of a system of psychological stability ("resilience") to potentially traumatic factors of professional activity and the prevention of negative consequences of combat and operational stress.Conclusions. The results of the analysis indicate the need for more effective coordination of the efforts of the relevant structures of the Armed Forces of Ukraine in order to make the organization of psychological training of military personnel conform to NATO standards.
Keywords: psychological training, resilience, psychological fitness, combat stress control, psychological readiness